2016
DOI: 10.1371/journal.pone.0168580
|View full text |Cite
|
Sign up to set email alerts
|

Genital Chlamydia trachomatis Infection among Women of Reproductive Age Attending the Gynecology Clinic of Hawassa University Referral Hospital, Southern Ethiopia

Abstract: BackgroundUrogenital infection with Chlamydia trachomatis(CT) is one of the most common bacterial sexually transmitted infections (STIs) world-wide, especially in developing nations where routine laboratory diagnosis is unavailable. Little is known about the epidemiology of this infection in Ethiopia where other STIs are prevalent. This study was conducted to determine the prevalence and associated factors of CT infection among women of reproductive age.MethodsA cross-sectional study was conducted among 322 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
5
11
3
Order By: Relevance
“…Consistent with previous reports [33, 34, 47, 48, 5153] being 18–25 years old was an independent risk factor of CT infection. In addition, being infected with NG and never tested for CT preciously were also independent risk factors of CT infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports [33, 34, 47, 48, 5153] being 18–25 years old was an independent risk factor of CT infection. In addition, being infected with NG and never tested for CT preciously were also independent risk factors of CT infection.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that 10.6% of men and 10.3% of women attending sexual and reproductive health clinics were tested positive for CT infection, similar to that reported in England (10.3%-10.6%) [38,40], Netherlands (8.9%-10.1%) [41], Nigeria (9.6%) [42], Danmark (11.5%) [43], Spain (12.3%) [44], Iran (12.6%) [45], and Mexico (14.2%) [46]. However, the prevalence of CT infection in the current study was higher than that reported in Australia (5.9%) [47] and lower than that reported in Ethiopia (18.9%) [48], Palestine (20.2%) [49] and Solomon Islands(20.3%) [50]. Compared to the previously reported prevalence of 17.7% in Shenzhen in 2009 [33], the current study found a much lower prevalence of CT infection, which may be related to improved access to health care for city residents.…”
Section: Discussionmentioning
confidence: 54%
“…In Ethiopia, the epidemiology of C. trachomatis and N. gonorrhoeae infection is not well described due to the asymptomatic nature of the infection and lack of laboratory diagnostic facilities. However, a hospital-based study that investigated women of reproductive age (15–49 years) reported prevalence of C. trachomatis and N. gonorrhoeae was 18.9 and 0.31%, respectively [11]. It would be important to study FCSWs to emphasize the need of strengthening intervention strategies that address the risk group.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the self-perceived high risk of STI acquisition, patients with STI-related symptoms may be more concerned about the outcomes of PN such as relationship breakdown and partner violence, and be more cautious about expressing their willingness to engage in PN. However, it was found that there was no association between symptoms and CT infection in many studies [19,[31][32][33][34], which means that asymptomatic patients can also be considered to have the same risk of CT infection as symptomatic patients. Because of the low level of awareness about CT infection (Knowledge Q1) in our study, asymptomatic individuals may underestimate their risk of CT infection, and may become cautious about participating in PN after they get diagnosed.…”
Section: Discussionmentioning
confidence: 99%